Ontogeny of lymphoid organs and mucosal associated lymphoid tissues in meagre (Argyrosomus regius). Issue 84 (January 2019) - Campoverde, Cindy; Andree, Karl B.; Milne, Douglas J.; Estévez, Alicia; Gisbert, Enric; Carella, Francesca
Abstract: This study investigates the development of lymphoid organs and mucosal tissues in larval and juvenile meagre, Argyrosomus regius . For this purpose, meagre larvae were reared from hatch to the juvenile stage, under mesocosm conditions at 18–19 °C, using standard feeding sequences with live prey and artificial food. The kidney was evident upon hatch and included a visible pronephros, with undifferentiated stem cells and excretory tubules at 1 dph (3.15 ± 0.1 mm SL). The thymus was first detected 8 dph (4.49 ± 0.39 mm SL) and was clearly visible 12 dph (5.69 ± 0.76 mm SL), 33 dph (15.69 ± 1.81 mm SL) an outer thymocytic zone and inner epithelial zone were visible. The spleen was present 12 dph, located between exocrine pancreas and intestine and by 26 dph (11.84 ± 1.3 mm SL) consisted of a mass of sinusoids filled with red blood cells. Melanomacrophage centers were found 83 dph (66.25 ± 4.35 mm SL) in the spleen. Between 14–15 dph (6.9 ± 1.1 mm SL), goblet and rodlet cells appear in the gill and intestinal epithelium. The lymphoid organs, which appear in the order of pronephric kidney (1 dph), thymus (8 dph) and spleen (12 dph) remarkably increase in size during the post-flexion stage. While functional studies are needed to confirm the activity of the immune response, the morphology of the lymphoid organs suggest that meagre is not immuno-competent until 83 dph. Highlights: The ontogeny of lymphoid organs of meagre larvae is generally similar among teleost fish. The appearance of the meagre thymus, kidney and spleen differs compared to a number of other teleost species. Knowledge of when tissue systems and lymphoid tissues develop of meagre larvae is crucial in larviculture management.